2016
DOI: 10.1371/journal.pone.0148169
|View full text |Cite
|
Sign up to set email alerts
|

Control of Somatosensory Cortical Processing by Thalamic Posterior Medial Nucleus: A New Role of Thalamus in Cortical Function

Abstract: Current knowledge of thalamocortical interaction comes mainly from studying lemniscal thalamic systems. Less is known about paralemniscal thalamic nuclei function. In the vibrissae system, the posterior medial nucleus (POm) is the corresponding paralemniscal nucleus. POm neurons project to L1 and L5A of the primary somatosensory cortex (S1) in the rat brain. It is known that L1 modifies sensory-evoked responses through control of intracortical excitability suggesting that L1 exerts an influence on whisker resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 94 publications
14
36
0
Order By: Relevance
“…It is well established that POm not only sends a direct input to vS1, but also modulates sensory processing in vS1 (Viaene et al, 2011;Castejon et al, 2016;Mease et al, 2016;Zhang & Bruno, 2019). Consistent with these studies, activation of SC increases activity of vS1 neurons, leading to larger whisker evoked responses particularly during small whisker movements.…”
Section: Discussionsupporting
confidence: 69%
“…It is well established that POm not only sends a direct input to vS1, but also modulates sensory processing in vS1 (Viaene et al, 2011;Castejon et al, 2016;Mease et al, 2016;Zhang & Bruno, 2019). Consistent with these studies, activation of SC increases activity of vS1 neurons, leading to larger whisker evoked responses particularly during small whisker movements.…”
Section: Discussionsupporting
confidence: 69%
“…Despite the physiological as well as morphological significance, the precise origins of GABAergic inputs as well as expression of Ca 2+ channel subtypes on their terminals in BF remains unknown. A recent study has demonstrated that P/Q‐type Ca 2+ channels are expressed on the axon terminal of parvalbumin (PV)‐containing interneurons in the cortex (Castejon et al ., ). PV‐containing neurons are also one of the important neuronal populations in the BF, sending GABAergic inputs to cholinergic neurons (Duque et al ., ; Zaborszky & Duque, ).…”
Section: Discussionmentioning
confidence: 95%
“…Numbers in parentheses indicate number of neurons examined. cortex (Castejon et al, 2016). PV-containing neurons are also one of the important neuronal populations in the BF, sending GABAergic inputs to cholinergic neurons .…”
Section: Mechanisms Independent Of Ca 2+ Influxmentioning
confidence: 99%
“…It is well established that POm not only sends a direct input to vS1, but also modulates sensory processing in vS1 [36][37][38][39] . Consistent with these studies, activation of SC increases activity of vS1 neurons, leading to larger whisker-evoked responses, particularly during small whisker movements.…”
Section: Discussionmentioning
confidence: 99%